Histomorphological patterns of endometrium in abnormal uterine bleeding - Murugan, Roopmala; Ramachandran, Thamilselvi; Inbasekaran, Poovizhi (Tropical Journal of Pathology and Microbiology, 2019)
Background: Abnormal uterine bleeding (AUB) is a common gynecological complaint, for which histopathological examination of endometrium is the gold standard tool in diagnostics. Aim: To analyze various histomorphological patterns of endometrium in patients belonging to various age groups with abnormal uterine bleeding. Materials and Methods: A retrospective study of 174 patients presenting with abnormal uterine bleeding underwent endometrial sampling during a period of 2 years from September 2017 to August 2019 at VMKVMCH, Department of Pathology, were analyzed. Endometrial tissue received by sampling procedures such as dilatation and curettage (D & C), endometrial biopsy and fractional curettage were all submitted entirely for processing in the Department of Pathology. Patient data were collected, and slides were reviewed. Result: A total of 174 cases were analyzed. Patients’ age ranged from 15 to 65 years. The predominant endometrial finding was proliferative endometrium 54 cases (31%) followed by secretory endometrium 50 cases (28.7%). Malignant lesions were seen in 5 cases (2.87%) in patients more than 49 years of age. Among the organic causes, polyps were the commonest 8 cases (4.59%). Adequate samples were obtained from 91% of cases while 9% of cases’ samples were inadequate for opinion. Conclusion: Histopathological examination of endometrial samples should be done in patients with abnormal uterine bleeding, especially in women over 35 years of age to rule out malignancy and preneoplasia. Patients with no organic pathology had normal physiological patterns like proliferative endometrium, secretory endometrium and menstrual changes. Most common endometrial pathology in this series was endometrial polyp 8 cases (4.59%).